Hubungan antara Ketahanan Pangan Keluarga dengan Status Gizi pada Anak SD Negeri 72 Kota Manado - Christina, Gabriela; Bolang, Alexander S. L.; Kawengian, Shirley E. S. (Medical Scope Journal, 2025)
Abstract: Household food security is a crucial factor influencing children’s nutritional status. This study aimed to analyze the correlation between household food security and the nutritional status of school-aged children at SD Negeri 72 Kota Manado. This was a cross-sectional study with a quantitative approach. Samples included 107 school-aged children and their parents. Food security status was measured using the US-HFSSM questionnaire, while nutritional status was assessed using BMI-for-age indicators. Data were analyzed using the chi-square test. The results showed that most children had good nutritional status (79.4%), although 60.7% of families were classified as food insecure. Statistical analysis indicated there was a significant correlation between household food security and children’s nutritional status (p=0.007). Despite a high prevalence of food insecurity among families, the children maintained good nutritional status, likely due to family prioritization of children’s needs and sufficient access to food in the area. In conclusion, there is a significant correlation between household food security and children’s nutritional status. Other factors, such as economy status, parenting and parental nutrition knowledge, may play a larger role in determining nutritional outcomes. Keywords: family food security; nutritional status; school-aged children Abstrak: Ketahanan pangan keluarga merupakan faktor penting yang dapat memengaruhi status gizi anak. Penelitian ini bertujuan untuk menganalisis hubungan antara ketahanan pangan keluarga dengan status gizi anak usia sekolah di SD Negeri 72 Kota Manado. Penelitian ini menggunakan desain potong lintang dengan pendekatan kuantitatif. Sampel terdiri dari 107 anak usia sekolah dan orang tua mereka. Ketahanan pangan diukur menggunakan kuesioner US-HFSSM, sedangkan status gizi diukur menggunakan indikator IMT/U. Analisis data dilakukan menggunakan uji chi-square. Hasil penelitian mendapatkan mayoritas anak memiliki status gizi baik (79,4%), meskipun 60,7% keluarga tergolong rawan pangan. Uji statistik menunjukkan terdapat hubungan bermakna antara ketahanan pangan keluarga dan status gizi anak (p=0,007). Meskipun sebagian besar keluarga tergolong rawan pangan, status gizi anak tetap baik. Hal ini dapat disebabkan oleh prioritas keluarga dalam memenuhi kebutuhan anak dan akses pangan yang memadai di lingkungan sekitar. Simpulan penelitian ini ialah terdapat hubungan antara ketahanan pangan keluarga dan status gizi anak. Faktor lain, seperti status ekonomi, pola asuh, dan pengetahuan gizi orang tua menunjukkan kecenderungan turut berperan dalam menentukan status gizi anak. Kata kunci: ketahanan pangan keluarga; status gizi anak; anak usia sekolah